2018
DOI: 10.1097/pec.0000000000001355
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Intubations in a High-Volume Pediatric Emergency Department

Abstract: All tracheal intubations performed were successful. Variance still exists in tracheal intubation practice. Further elucidation of patient, practice, and provider factors will aid development of a bundle quality improvement intervention directed at addressing these factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…As intubation for children is a rare event (e.g., 2–33/10,000 ED visits), emergency physicians are likely unfamiliar with airway management in children. Additionally, the highly stressed clinical situation within limited resources might further contribute to low success rates and errors, such as miscalculation for medication doses .…”
Section: Special Circumstance: Childrenmentioning
confidence: 99%
“…As intubation for children is a rare event (e.g., 2–33/10,000 ED visits), emergency physicians are likely unfamiliar with airway management in children. Additionally, the highly stressed clinical situation within limited resources might further contribute to low success rates and errors, such as miscalculation for medication doses .…”
Section: Special Circumstance: Childrenmentioning
confidence: 99%
“…Matettore et al 3 had reported adverse tracheal intubation‐associated events to be more common in pediatric patients presenting to non‐specialist centers. However, this finding was not replicated and may be explained by the lower frequency of intubation among pediatric patients as compared to adult patients 12‐14 . Consequentially, emergency physicians in general EDs would be more experienced with emergency airway management even though they may be less familiar with intubation in pediatric patients.…”
Section: Discussionmentioning
confidence: 89%
“…However, this finding was not replicated and may be explained by the lower frequency of intubation among pediatric patients as compared to adult patients. [12][13][14] Consequentially, emergency physicians in general EDs would be more experienced with emergency airway management even though they may be less familiar with intubation in pediatric patients. They were thus able to apply principles and techniques to facilitate intubation in these critically ill pediatric patients, leading to a similar success rate with a lower rate of adverse tracheal intubation-associated events as compared to the pediatric ED.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric endotracheal intubations in the ED are relatively infrequent compared to adult intubations. 2 , 3 A recent study of 43 EDs in Australia and New Zealand showed that pediatric intubations accounted only for 4.94% (270/5463) of all total intubations. 2 This presents a problem to practitioners who manage pediatric patients, as they have fewer opportunities to “practice” real‐life pediatric intubations.…”
Section: Introductionmentioning
confidence: 99%